France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
The export performance of the French economy relative to its own past and relative to a major trading partner, Germany, has deteriorated. The risk analysis indicates that French firms have seen a significant improvement in the corporate health, and seem resilient to the recent financial shock despite differences across firms. Several issues in the context of common EU tax policy formation, including carbon pricing, control problems associated with the zero-rating of intra-EU supplies, and possible movement toward a common corporate tax base need to be addressed.